Knockdown of SNORA47 Inhibits the Tumorigenesis of NSCLC via Mediation of PI3K/Akt Signaling Pathway - Yu, Huiqing; Tian, Ling; Yang, Liejun; Liu, Shihong; Wang, Sixiong; Gong, Juan (Frontiers in Oncology, 2021)
Background: Non-small cell lung cancer (NSCLC) is a frequently diagnosed aggressive cancer all over the world. Small nucleolar RNAs (snoRNAs) are a group of non-coding mediatory RNAs. A previous report indicated that small nucleolar RNA 47 (SNORA47) is upregulated in NSCLC. However, the role of SNORA47 in NSCLC is unclear. Material and methods: Cell proliferation was measured by immunofluorescence staining. Cell apoptosis and cycle of NSCLC were tested by flow cytometry and the protein expressions were investigated by Western-blot. Meanwhile, cell migration and invasion were detected by transwell assay. Xenograft mice model was established to detect the effect of SNORA47 knockdown on tumor growth of NSLC in vivo. Results: Knockdown of SNORA47 significantly inhibited the proliferation of NSCLC cells via inducing cell apoptosis. Moreover, migration and invasion of NSCLC cells were notably decreased by SNORA47 shRNA. SNORA47 knockdown significantly induced G1 arrest in NSCLC cells via regulation of p27 Kip1, CDK2 and cyclin D1. Meanwhile, SNORA47 shRNA inhibited EMT process and PI3K/Akt signaling in NSCLC cells. Finally, silencing of SNORA47 significantly inhibited the tumor growth of NSCLC in vivo. Conclusion: Knockdown of SNORA47 significantly inhibited the tumorigenesis of NSCLC via inhibition of PI3K/Akt signaling and EMT process. Thereby, our finding might shed a new light on exploring the strategies for the treatment of NSCLC.